Handbook of human factors and ergonomics - Salvendy, Gavriel, 1938- (Hoboken : John Wiley & Sons, 2012)
The fourth edition of the Handbook of Human Factors and Ergonomics has been completely revised and updated. This includes all existing third edition chapters plus new chapters written to cover new areas. These include the following subjects: Managing low-back disorder risk in the workplace, Online interactivity, Neuroergonomics, Office ergonomics, Social networking, HF & E in motor vehicle transportation, User requirements, Human factors and ergonomics in aviation, Human factors in ambient intelligent environments. As with the earlier editions, the main purpose of this handbook is to serve the needs of the human.
Chapter 53 Designing for Children.
Includes bibliographical references and index.
Print version record.
Keywords: Human engineering -- Handbooks, manuals, etc; Ergonomics -- Guides, manuals, etc; Human engineering; Civil engineering; Engineering; TECHNOLOGY & ENGINEERING -- Industrial Design -- General; Human engineering; Human Engineering; Electronic books; Handbooks and manuals; Electronic books